Ajar-Ajaren Simehuli Of Karo Tribe To Elementary Age Children - Assingkily, Muhammad Shaleh; Putro, Khamim Zarkasih; Barus, Uni Sahara Br; Assingkily, Maiyatul Jannah (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
Ajar-ajaren simehuli are an oral tradition in the form of advice that is commonly given to children from an elementary age children. This article aims to examine the ajar-ajaren simehuli in the customs and religious rituals of the Karo tribe for elementary children in Serdang Village, Barusjahe Subdistrict, Karo District. The formulation of the problem in this research is what are the teachings of ajar-ajaren simehuli Karo people in Serdang Village, Barusjahe Subdistrict, Karo District, how ajar-ajaren simehuli are given to young children, and why the oral tradition of conveying ajar-ajaren simehuli is preserved. This study uses a qualitative approach with a research background in Serdang Village, Barusjahe Subdistrict, Karo District. This results of this study indicate that ajar-ajaren simehuli were entrenched for the Karo tribe community, including (1.a) mari man, ula perjat juma kalak, ula buet barang kalak, ngisahken si mbarenda, and mereken perembah, (1.b) ndahi kalimbubu mbereken kehamaten, (1.c) bujur, nggit nampati, elem-elem, motong rambai, and erpangir ku lau. Furthermore, (2) ajar-ajaren simehuli are given through oral traditions, exemplary attitudes, and cultural and religious rituals. (3) preservation of ajar-ajaren simehuli the Karo community begins with the family environment and also includes traditional, religious and government leaders believed to be guarding the ancestral messages that children need as a provision to ‘wade-through’ life.